2014
DOI: 10.1037/law0000021
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of rapport-based techniques for minimizing counter-interrogation tactics amongst a field sample of terrorists.

Abstract: The impact of rapport-based interview techniques on suspect use of counter-interrogation tactics (CITs) was examined in an operational field sample of 181 police interrogations with international (Al-Qaeda and Al-Qaeda-inspired), paramilitary, and right-wing terrorists. The observing rapport-based interpersonal techniques (ORBIT) framework was used to code rapport-based interrogator skills along 2 dimensions: motivational interviewing skills and interpersonal competence (use of adaptive interviewing behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 29 publications
4
74
1
Order By: Relevance
“…As described previously, a strong foundation of research has been established with respect to interviewing cooperative subjects (see Powell et al, 2005); however, much of this research has focused on skills related to interviewing witnesses or victims. While interrogation training programs primarily focus on gaining cooperation (and ultimately a state of compliance that produces a confession; see , researchers have begun to assess the importance of basic elicitation skills in promoting conversational rapport in less cooperative contexts -including the use of effective questioning skills drawn from a Motivational Interviewing framework (discussed previously;Alison et al, 2013Alison et al, , 2014. We focus here on research that has extended the Cognitive Interview to subject interviews for eliciting criminal and intelligence information.…”
Section: Eliciting Information Via Conversational Rapport and Facilitmentioning
confidence: 99%
“…As described previously, a strong foundation of research has been established with respect to interviewing cooperative subjects (see Powell et al, 2005); however, much of this research has focused on skills related to interviewing witnesses or victims. While interrogation training programs primarily focus on gaining cooperation (and ultimately a state of compliance that produces a confession; see , researchers have begun to assess the importance of basic elicitation skills in promoting conversational rapport in less cooperative contexts -including the use of effective questioning skills drawn from a Motivational Interviewing framework (discussed previously;Alison et al, 2013Alison et al, , 2014. We focus here on research that has extended the Cognitive Interview to subject interviews for eliciting criminal and intelligence information.…”
Section: Eliciting Information Via Conversational Rapport and Facilitmentioning
confidence: 99%
“…Regarding criminal suspects, a questionnaire completed by 631 police investigators in the USA revealed that establishing rapport was reported as the fourth most commonly used tactic, with 32% of investigators revealing that they always build rapport during an interrogation (Kassin et al, ). Subsequent studies have also established the frequent use and benefits of rapport‐building with criminal suspects (Alison et al, ; Alison et al, in press; Bull & Soukara, ; Kelly et al, ; Walsh & Bull, , ), suggesting that building and maintaining rapport throughout the criminal interview can increase successful interview outcomes. Despite the perceived importance and actual usage of rapport‐building, relatively little is known regarding specific rapport‐building techniques used by law enforcement interviewers during witness interviews and suspect interrogations.…”
Section: Introductionmentioning
confidence: 98%
“…The interviewer's goal here is to reduce the likely intensity of the emotion‐laden discourse; he can do this by active listening, not shouting back, and echoing the key words. (b) The interviewer might challenge the subject on some aspect of his identity: for example, he might say, “You've said you are a good father and that you love your daughter, but not telling us what might have happened last night may make it only harder for us to find her now.” The goal of this challenge is not to be confrontational or draw the subject into an argument, but to engage him—at least now both interviewer and subject are on the same topic; this may also create some cognitive dissonance (Festinger, ). Talks about apparently irrelevant topics, retracts previous statements: To redirect the conversation away from the topic at hand is a strategy not only just of criminal subjects (Alison et al, ) but also of politicians (Norton & Goethals, ). Interviewer counter‐strategies might be (a) assuming a position of “seeking guidance”: “I told you why we are here today; can you help me understand why you choose not to talk to me?” (Alison et al, ) or by (b) pointing to inconsistencies, using evocation—that is, drawing out the subject's beliefs and feelings (Miller & Rollnick, ). Tries to manipulate the relationship with the interviewer, faults the interviewer, denies all knowledge and responsibility: The interviewer might reframe the exchange by suggesting that the subject is believed to have the most knowledge about the event in question and, in this instance, is the “expert,” or point out that he (the interviewer) is being asked to conduct the interview on behalf of the officer‐in‐charge (Sprecher, ).…”
Section: The Interviewmentioning
confidence: 93%
“…• Talks about apparently irrelevant topics, retracts previous statements: To redirect the conversation away from the topic at hand is a strategy not only just of criminal subjects (Alison et al, 2014) but also of politicians (Norton & Goethals, 2004). Interviewer counter-strategies might be (a) assuming a position of "seeking guidance": "I told you why we are here today; can you help me understand why you choose not to talk to me?"…”
Section: Start the Conversation And Then Listenmentioning
confidence: 98%